Pengaruh Ukuran Perusahaan, Umur Perusahaan, Laba dan Arus Kas terhadap Kondisi Financial Distress: Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi - Hanifa Ramadhany; Efrizal Syofyan (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to determine the effect of company size, company age, profit, and cash flow on financial distress conditions carried out by manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. The population of this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2017 – 2019. The sample is determined using the purposive sampling method consisted of 46 companies. The results showed that firm size, profit and cash flow has a negative effect on financial distress conditions. While the age of the company has no effect on the condition of financial distress.